Vatican II: Renewal Within Tradition - Lamb, Matthew L. (Oxford University Press USA - OSO, 2008)
In Vatican II: Renewal Within Tradition, an international team of theologians challenges the standard view of the Council as causing a rupture with earlier Catholic teaching. Examining each document issued, they argue that The Council was indeed putting forth a vision for the future of the Church, but that vision was grounded in two millennia of tradition. Taken together, these essays demonstrate that Vatican II's documents are a development from an established antecedent in the Roman Catholic Church. Each chapter contextualizes Vatican II teachings within that rich tradition.